PENILAIAN KESEJAHTERAAN HEWAN PADA PENYEMBELIHAN HEWAN KURBAN DI BEBERAPA GAMPONG DI KOTA BANDA ACEH (THE EVALUATION OF ANIMAL WALFARE IN QURBAN ANIMAL SLAUGHTERING AT SOME VILLAGES IN BANDA ACEH CITY) - Roy Tigana Putra; Razali Razali; T. Reza Ferasyi; Fakhrurrazi Fakhrurrazi; Ismail Ismail; Ginta Riady; M Daud AK (JURNAL ILMIAH MAHASISWA VETERINER, 2021)
ABSTRAKPenelitianinibertujuanmenilaipenerapan kesejahteraan hewan padapenyembelihanhewankurbantahun 2018 di 17 Gampong di Kota Banda Aceh.Metodeyang digunakandalampenelitianiniadalahmetodesurveymenggunakan data check list dankuesioner. Data hasilsurveydikelompokkankedalamtigakategoriyaitu. kesehatan hewan, penanganan hewan hidup  dan proses penyembelihan. Data yang diperolehdianalisissecaradeskriptif.  Hasilanalisischeck listmenunjukkanbahwaketigaaspek yang dinilaimendapatkanhasilpenilaian yang buruk. Berdasarkankuisionerdidapatbahwa 70,6%tempatpenyembelihanhewankurbanbelummemilikikandangkhususuntukpenampunganhewansebelumdisembelih. Bahwasebesar82,4% tempatpenyembelihanterpisahtidakjauhataudapatdilihatolehsapi lain. Kemudiansebesar82,4% saat hewan tiba tidak disediakan tempat penurunan hewan dari truk.Dapatdisimpulkanbahwapenyembelihanhewankurbantahun 2018 di Banda Aceh belum menerapkanaspekkesejahteraan hewan.Kata Kunci: Kesejahteraan, penampungan,penyembelihan, kurban, Banda AcehABSTRACTThis study aims to assess the application of animal welfare to the slaughter of sacrificial animals in 2018 in 17 villages in the city of Banda Aceh. The method used in this study is the survey method using data check lists and questionnaires. The survey data are grouped into three categories, namely. animal health, handling live animals and the slaughter process. The data obtained were analyzed descriptively. The results of the check list analysis show that the three aspects assessed get poor results. Based on the questionnaire it was found that 70.6% of slaughterhouses for sacrificial animals did not have speciallairagefor animal shelter before being slaughtered. Whereas 82.4% of the slaughterhouses are not far apart or can be seen by other cows. Then 82.4% when animals arrive, there is no place for dropping animals from trucks. It can be concluded that the slaughter of sacrificial animals in 2018 in Banda Aceh has not yet applied aspects of animal welfare. Keywords: Welfare, shelter, slaughter, sacrifice, Banda AcehABSTRAKPenelitianinibertujuanmenilaipenerapan kesejahteraan hewan padapenyembelihanhewankurbantahun 2018 di 17 Gampong di Kota Banda Aceh.Metodeyang digunakandalampenelitianiniadalahmetodesurveymenggunakan data check list dankuesioner. Data hasilsurveydikelompokkankedalamtigakategoriyaitu. kesehatan hewan, penanganan hewan hidup  dan proses penyembelihan. Data yang diperolehdianalisissecaradeskriptif.  Hasilanalisischeck listmenunjukkanbahwaketigaaspek yang dinilaimendapatkanhasilpenilaian yang buruk. Berdasarkankuisionerdidapatbahwa 70,6%tempatpenyembelihanhewankurbanbelummemilikikandangkhususuntukpenampunganhewansebelumdisembelih. Bahwasebesar82,4% tempatpenyembelihanterpisahtidakjauhataudapatdilihatolehsapi lain. Kemudiansebesar82,4% saat hewan tiba tidak disediakan tempat penurunan hewan dari truk.Dapatdisimpulkanbahwapenyembelihanhewankurbantahun 2018 di Banda Aceh belum menerapkanaspekkesejahteraan hewan.Kata Kunci: Kesejahteraan, penampungan,penyembelihan, kurban, Banda Aceh ABSTRACTThis study aims to assess the application of animal welfare to the slaughter of sacrificial animals in 2018 in 17 villages in the city of Banda Aceh. The method used in this study is the survey method using data check lists and questionnaires. The survey data are grouped into three categories, namely. animal health, handling live animals and the slaughter process. The data obtained were analyzed descriptively. The results of the check list analysis show that the three aspects assessed get poor results. Based on the questionnaire it was found that 70.6% of slaughterhouses for sacrificial animals did not have speciallairagefor animal shelter before being slaughtered. Whereas 82.4% of the slaughterhouses are not far apart or can be seen by other cows. Then 82.4% when animals arrive, there is no place for dropping animals from trucks. It can be concluded that the slaughter of sacrificial animals in 2018 in Banda Aceh has not yet applied aspects of animal welfare.Keywords: Welfare, shelter, slaughter, sacrifice, Banda Aceh